PKM Development of Herb Business Traditional Buffer Area Forest Leuser - Yayuk Yuliana; Wan Dian Safina; Minda Sari Lubis (LPPM UIKA Bogor, 2022)
The Tambar Malem group, which currently consists of housewives still producing traditional Karo concoctions. This group is located in Batu Katak Hamlet, Batu Jong Jong Village. Potions- potions produced by the Medicinal Plant Cultivation Group and produce it Becomes worthy for for sale moment it still is belong simple. Plant The ingredients cultivated are turmeric, galangal, kencur, bengle, temu Kunci, lemon grass, wake-up leaves. get up and other types. Materials are collected from the garden or purchased and then washed and cleaned then processed manually using simple tools such as machetes, knives and swallow. The nutritious rhizomes and leaves are chopped on the chopping board with a machete. After it is felt that these ingredients get the desired texture as a whole the ingredients are mixed into one so that the ingredients are evenly mixed. After this process, do it drying that still relies on solar energy to dry the material. that way is one of the process of making spray. The problems faced are the method of production, still using traditional methods. In production still use simple tools and manual so the amount of production is still small. Methods of implementation using education and counseling, and training. Solutions to partner priority problems from Aspect production ie with procurement and use of equipment. The result achieved is an increase in the quality of the herb product.